Short Chain (≤C4) Esterification Increases Bioavailability of Rosmarinic Acid and Its Potency to Inhibit Vascular Smooth Muscle Cell Proliferation - Blažević, Tina; Reznicek, Gottfried; Ding, Limin; Yang, Gangqiang; Haiss, Patricia; Heiss, Elke H.; Dirsch, Verena M.; Liu, Rongxia (Frontiers in Pharmacology, 2021)
Rosmarinic acid is a natural phenolic acid and active compound found in many culinary plants, such as rosemary, mint, basil and perilla. Aiming to improve the pharmacokinetic profile of rosmarinic acid and its activity on vascular smooth muscle cell proliferation, we generated a series of rosmarinic acid esters with increasing alkyl chain length ranging from C1 to C12. UHPLC-MS/MS analysis of rat blood samples revealed the highest increase in bioavailability of rosmarinic acid, up to 10.52%, after oral administration of its butyl ester, compared to only 1.57% after rosmarinic acid had been administered in its original form. When added to vascular smooth muscle cells in vitro, all rosmarinic acid esters were taken up, remained esterified and inhibited vascular smooth muscle cell proliferation with IC50 values declining as the length of alkyl chains increased up to C4, with an IC50 of 2.84 µM for rosmarinic acid butyl ester, as evident in a resazurin assay. Vascular smooth muscle cells were arrested in the G0/G1 phase of the cell cycle and the retinoblastoma protein phosphorylation was blocked. Esterification with longer alkyl chains did not improve absorption and resulted in cytotoxicity in in vitro settings. In this study, we proved that esterification with proper length of alkyl chains (C1-C4) is a promising way to improve in vivo bioavailability of rosmarinic acid in rats and in vitro biological activity in rat vascular smooth muscle cells.